Business & Society. Stakeholders, Ethics, Public policy - LAWRENCE, Anne T (McGraw - Hill Book Company, 2011)
"Business and Society: Stakeholders, Ethics, Public Policy, 13e" by Lawrence and Weber has continued through several successive author teams to be the market-leader in its field. "Business and Society, 13e" highlights why government regulation is sometimes required as well as new models of business-community collaboration. The authors believe that businesses have social (as well as economic) responsibilities to society; that business and government both have important roles to play in the modern economy; and, that ethics and integrity are essential to personal fulfillment and to business success. In addition, this textbook has long been popular with students because of its lively writing, up-to-date examples, and clear explanations of theory.